EDUCATIONAL MANAGEMENT FUNCTIONS: PLANNING, ORGANIZING, ACTUATING, CONTROLLING - Nurhikmah, Nurhikmah (INTIHA: Islamic Education Journal, 2024)
Education management is a key element in managing, organizing and administering educational institutions to achieve the desired educational goals effectively and efficiently. The research method used is library research, which involves collecting information from various sources such as books, notes, magazines and related articles. Data collection techniques are carried out by reading, reviewing and analyzing various existing literature. The data analysis technique used is content analysis. This article explains the functions of educational management including planning, organizing, actuating and controlling. Educational planning involves setting goals, identifying necessary resources, and designing strategies to achieve those goals. Organizing regulates the organizational structure, division of tasks, and allocation of resources to support the teaching and learning process. Movement involves motivating, directing, and coordinating individual and group efforts in achieving educational goals. Control is the process of monitoring and evaluating performance to ensure that educational goals are in accordance with plans. Evaluation serves to assess the effectiveness of educational programs, identify strengths and weaknesses, and provide a basis for improvement and further development. A deep understanding of the functions of educational management can help educational leaders manage their institutions effectively and efficiently so that they are able to achieve success in providing quality education for future generations.